Use of Idioms in the Poetry of Syed Khaliqdad Umeed - Uddin, Shahab; Ahmad, Mazhar (sourcecoder, 2024)
An idiom is a type of phrase or expression that has a meaning that can’t be deciphered by defining the individual words, and An idiom can be used in dialogue to give more insight into who a character is. Syed Khaliqdad Umeed has used idioms in a new way in his poetry. In this paper, the use of idioms in the poetry of Syed Khaliqdad Umeed has been researched.